The Perception of Islamic Schools and Its Influence on Students’ Interest in Continuing Education at State Islamic Senior High Schools - Heru Juabdin Sada; Citra Kartika Diantari; Nirva Diana; Ryuzen Praja Tuala (SAKAGURU: Journal of Pedagogy and Creative Teacher, 2024)
The perception of a school represents how society evaluates an institution or organization based on experiences and observations, creating either a positive or negative impression that impacts the institution's sustainability. Students’ interest can be defined as their intrinsic inclination to select the best educational institution, which emerges consciously from within. This study aims to analyze the influence of Islamic school perception on students’ interest in continuing their education at MAN 1 Lampung Tengah for the 2023/2024 academic year. A quantitative research method was employed, using random sampling techniques and Slovin's formula. The study population comprised 427 tenth-grade students, with a sample size of 207 students. Data were collected using a Likert-scale questionnaire with four response options. Validity tests utilized the Pearson Product-Moment correlation, and reliability tests were conducted using Cronbach's Alpha, supported by SPSS software version 20. Data were analyzed through simple linear regression and coefficient of determination. The results revealed a calculated t-value of 4.587 with a significance level of 0.00, while the critical t-value at df = 205 and α = 0.05 was 1.652. Since tcalculated > ttable (4.587 > 1.652) and the significance level of 0.00 < 0.05, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted. The correlation coefficient was 0.307 with a constant of 37.458, indicating that a 1% increase in school perception (X) would enhance student interest (Y) by 0.307. The coefficient of determination (R²) was 28.7%, showing that school perception positively influenced students' interest, while the remaining 71.3% was attributed to other factors not examined in this study. In conclusion, the perception of Islamic schools significantly affects students’ interest in continuing their education at MAN 1 Lampung Tengah. These findings underscore the importance of efforts by Islamic schools to build a positive image to enhance their appeal and attract prospective students